PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN LEMBAR KERJA PESERTA DIDIK (LKPD) DISERTAI MIND MAP PADA MATERI JAMUR TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS X - Wijayanti, Tutik Fitri; Sukron, Sukron; Abadi, Suyud (Cocos Bio, 2022)
This study aims to determine the effect of the Problem Solving learning model assisted by StudentWorksheets accompanied by a mind map on mushroom material on the cognitive learning outcomes ofstudents in class X SMA Negeri 1 Pemulutan Selatan. The method used is Quasi Experiment with Nonequivalent control group design. Sampling in this study using purposive sampling technique. The results ofthis study were obtained from the calculation of the paired t-test (Paired Sample t-Test) in the experimentalclass with (α = 0.05) the significance value (2-tailed) was 0.000 <0.05. The correlation value in the PairedSample Correlations table obtained from the pretest and posttest scores of students in the experimental classis 0.22592 = 0.05 (5%), so that 5% problem solving learning model assisted by Student Worksheetsaccompanied by a mind map has an effect on learning outcomes. students of SMA Negeri 1 PemulutanSelatan.